Lessons learned from health system rehabilitation preparedness and response for disasters in LMICs: a scoping review - Gosling, Justine; Maritz, Roxanne; Laplante-Lévesque, Ariane; Sabariego, Carla (BMC public health, 2024)
Disasters such as earthquakes, conflict, or landslides result in traumatic injuries creating surges in rehabilitation and assistive technology needs, exacerbating pre-existing unmet needs. Disasters frequently occur in countries where existing rehabilitation services are underdeveloped, hindering response to rehabilitation demand surge events. The primary aim of this scoping review is therefore to synthesize the evidence on rehabilitation and assistive technology preparedness and response of health systems in LMICs to the demand associated with disasters and conflict situations. A secondary aim was to summarize related recommendations identified in the gathered literature. A scoping review was conducted using the Arksey and O'Malley framework to guide the methodological development. The results are reported in accordance with PRISMA-ScR. Four bibliographic databases were used: CINHAL, Cochrane, Pubmed, Scopus and. Key international organisations were also contacted. The search period was from 2010-2022. Eligible publications were categorized for analysis under the six World Health Organization health systems buildings blocks. The findings of this scoping review suggest that rehabilitation is poorly integrated into health systems disaster preparedness and response in LMICs. Of the 27 studies included in the scoping review, 14 focused on service delivery, 6 on health workforce, 4 on health information systems and 3 on the leadership and governance building block. No study focused on financing nor assistive technology. This review found the most frequently referenced recommendations for actions that should be taken to develop rehabilitation services in disasters to be: the provision early and multi-professional rehabilitation, including the provision of assistive technology and psychological support, integrated community services; disaster response specific training for rehabilitation professionals; advocacy efforts to create awareness of the importance of rehabilitation in disasters; and the integration of rehabilitation into disaster preparedness and response plans. Findings of this scoping review suggest that rehabilitation is poorly integrated into health systems disaster preparedness and response in LMIC's, largely due to low awareness of rehabilitation, undeveloped rehabilitation health systems and a lack of rehabilitation professionals, and disaster specific training for them. The paucity of available evidence hinders advocacy efforts for rehabilitation in disaster settings and limits the sharing of experiences and lessons learnt to improve rehabilitation preparedness and response. Advocacy efforts need to be expanded.